Penerapan Teams Games Tournament Untuk Meningkatkan Kemampuan Berpikir Analitis Siswa Kelas XB Mata Pelajaran SKI - Arsyid, Raodah; Syafruddin, Syafruddin; Khairudin, Khairudin (Educatio, 2025)
This study aims to improve the analytical thinking skills of class XB students of MA Darul Hikmah Kota Bima through the implementation of a cooperative approach of the Teams Games Tournament type. The type of research uses Classroom Action Research which is carried out in two cycles, with each cycle consisting of four stages, namely: planning, implementation of actions, observation, and reflection. The data analysis technique used is quantitative descriptive. The findings of the pre-cycle stage of the study showed that the achievement of student learning completeness was still relatively low, which was 33.3%. After the implementation of the action in cycle I, there was an increase in completeness reaching 54.2%. This increase continued until cycle II, where completeness increased to 83.3%. From these results, it can be concluded that the implementation of the cooperative approach of the Teams Games Tournament type succeeded in improving the analytical thinking skills of class XB students of MA Darul Hikmah Kota Bima